Educational pathways and decisions - Comparing the returns of investment in Germany and Canada - Annen, Silvia [Verfasser]; Tiemann, Michael [Verfasser] (My University, 2017)
This paper presents results from a project which analyses the career paths of employees in commercial occupations focussing on the competition between vocational and higher education. "Within the project qualification and skill utilization of the respective educational programmes shall be evaluated with regard to occupational status and positions as well as income. The research concept contains curricula and vacancies analyses, case studies and a quantitative survey. The theoretical background is formed by the signaling and screening approach as well as the segmentation theory. This paper analyses data from the qualification and career survey of 2011/2012 and focuses on employees' income. From an individual perspective the monetary outcomes of persons with equivalent qualifications are compared. Equivalence of qualifications refers to the German National Qualification Framework (GQF). To find comparable occupational positions the national classification of occupations [Klassifikation der Berufe - KldB] which includes information on qualificational requirements is used. The results are compared with respective data from Canada." (Authors' abstract, BIBB-Doku)
Keywords: S 6.4.1 Kaufleute; G 1.3.3.1 Qualifikationsverwertung; G 1.2.2 Beschäftigungs- und Arbeitsverhältnisse; T 1.5 International vergleichende Berufsbildungsforschung; I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; I 2.3.2 Nordamerika; Kaufmännischer Beruf; Ausbildungsabsolvent; Hochschulabsolvent; Bachelor; Qualifikationsverwertung; Einkommen; BIBB-/BAuA-Erhebung; Vergleichende Berufsbildungsforschung; Internationaler Vergleich; Bundesrepublik Deutschland; Kanada